Personal Responsibility : Why It Matters. - Brown, Alexander (Think Now Ser., 2009)
Personal responsibility is now very much on the political agenda. But what is personal responsibility? Why do we care about it? And what, if anything, should governments do to promote it?. This book explores the idea that individuals bear a special responsibility for the success or failure of their own lives looking at philosophical theories, political ideologies and public opinion on the subject. Alexander Brown lends support to a recent move in political philosophy to deal with real world problems and shows how philosophy can contribute to public democratic debate on pressing issues of perso.